2022
DOI: 10.1016/j.heliyon.2022.e08845
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of environmental Vibrio species – antibiotic resistance

Abstract: Adequate comprehension of the genomics of microbial resistance to an antimicrobial agent will advance knowledge on the management of associated pathologies and public health safety. However, continued emergences and reemergence of pathogens, including Vibrio species, hallmarks a potential knowledge gap. A clear understanding of the process and forecast of the next trend should be in place to nip in the bud, microbial acquisition of resistance to antibiotics. Therefore, this two-decade (1 January 2000 to 31 Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 47 publications
2
26
0
Order By: Relevance
“…Likewise, resistance gens codings for sulfonamides were also found in these water sources (Figure ). In addition, we also observed the presence of A. hydrophila and A. veronii in one of the tertiary treated municipal wastewater sites (MA06) that was predicted to carry beta lactam resistance genes (Figure ), which has been documented in multiple studies. Previous studies have also described the presence of Vibrio species (in wastewater effluent and surface waters) carrying sulfonamide resistance genes. Similarly, our study identified Vibrio species ( V. fluvialis and V. cholerae ) in Southwest return flows that were predicted to carry sulfonamide resistance genes (Figure ).…”
Section: Discussionsupporting
confidence: 74%
“…Likewise, resistance gens codings for sulfonamides were also found in these water sources (Figure ). In addition, we also observed the presence of A. hydrophila and A. veronii in one of the tertiary treated municipal wastewater sites (MA06) that was predicted to carry beta lactam resistance genes (Figure ), which has been documented in multiple studies. Previous studies have also described the presence of Vibrio species (in wastewater effluent and surface waters) carrying sulfonamide resistance genes. Similarly, our study identified Vibrio species ( V. fluvialis and V. cholerae ) in Southwest return flows that were predicted to carry sulfonamide resistance genes (Figure ).…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of antibiotic-resistant genes is likely achieved through horizontal transfer from other bacteria strains in the aquatic environment [ 71 ]. Genetic interactions leading to the acquisition of plasmids, transposable elements, super-integron and integrating conjugative elements (ICEs) gene can confer antibiotic resistance to Vibrio species [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the intermediate phenotypic range on meropenem and resistance in other carbapenem antibiotics indicates resistance determinants. Such a high level of antibiotic resistance phenotype to the carbapenem antibiotics has become a significant cause of health concern as it resulted in aggravated infection cases and a challenge to treat situation 11 , 37 in a disease implication. Following the reports of Shah et al and his group on related studies, it was affirmed that such increased resistant phenotypes might result in increased volume and incidence of hospitalized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Klebsiella pneumoniae was the first organism reported to harbor the first documented NDM-1 gene. It is expressed in organisms that harbor them with the following features; a broad spectrum of aminoglycoside resistance enzymes such as acetyltransferases and methylases, and topoisomerase mutations leading to a high level of resistance 5 , 10 , 11 resistance to carbapenem and β-lactam antibiotics were the produce carbapenemase and β-lactamase. 5 , 11 NDM-1, like most enzymes, requires metal-based cofactors to carry out catalytic reactions (in the presence of the zinc ions), hence the term “Metallo.” 12 NDM-1 is involved in the inactivation of the beta-lactams ring while excluding aztreonam.…”
Section: Introductionmentioning
confidence: 99%